I think this is somewhat similar to a suggestion of Nick Coghlan's. One
possible syntax as a statement might be:
y = b + 2 given:
b = a + 1
Just to get this right: this proposal is about
reversing the order of chaining expressions? Instead of: b = a + 1 c = b + 2 we could write it in reverse order: c = b + 2 given/for: b = a + 1
If so, I don't know if it just complicates the language with a
feature which does not save writing nor reading nor cpu cycles nor
memory and which adds a functionality which is already there (but
in reverse order).
Maybe there are more benefits I don't see right now.